ANALISIS KEMAMPUAN GURU AKIDAH AKHLAK DALAM PENYUSUNAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) KURIKULUM 2013 DI MTs NEGERI KOTA PALOPO - arifuddin arifuddin (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2020)
Abstract: The purpose of this study was to analyze the ability of teachers of the Islamic Morals in preparing the 2013 Curriculum Lesson Plan (RPP) in MTs Negeri Kota Palopo by using descriptive qualitative research methods. The qualitative descriptive method is a method used in research to analyze a problem that occurs and describe it based on data obtained from the results of research in the form of written or oral words of the problem being studied / traced. The author was conducted the research data collection by using 3 (three) instruments, namely observation, interviews, and documentation. The results showed that the ability of teachers of the Islamic Morals in preparing the 2013 Curriculum Lesson Plan (RPP) in the MTs Negeri Kota Palopo was categorized as "good" with 3 (three) stages of observation by the writer. The results of the first observation score were 86%, the second was 78%, and the third was 86% with an average score of 83.33% achievement ability, this is evident from the completeness of the Lesson Plan (RPP) made by the teacher concerned. However the ability achieved is not necessarily obtained directly without being influenced by several factors. This achievement was based on 2 (two) factors which consist of internal factors and external factors. Internal factors included teacher understanding of the preparation of lesson plans, teachers had not to be innovative yet  in the learning process, and the ability of teachers to manage classrooms. The external factors included limited time, lacked of availability of media in schools, and the conditions and characteristics of students.